ANALISIS RISIKO KECELAKAAN MENGGUNAKAN METODE JOB RISK ASSESSMENT PADA PELAKSANAAN PROYEK PEMASANGAN PIPA GAS PADA PT. XYZ DI TANGERANG - Liku, James Everd Adolf Everd Adolf; Pongky, Patunru Pongky (Program Studi Kesehatan dan Keselamatan Kerja, 2019)
Accident risk analysis using the job risk assessment method on the implementation of the gas pipe installation project at PT. XYZ Tangerang. This study discusses the value of risk from each stage of the gas pipe installation work carried out by PT. XYZ in 2014. Risk assessment is done by analyzing the probability value, exposure, and consequences of each stage of the gas pipe installation work which is then categorized according to the AS/NZS 4360 semi-quantitative risk level standard on Risk Management to determine the level of risk at each stage of work gas pipe installation. This study is a descriptive analytic study using the AS/NZS 4360: 2004 semi-quantitative method. The results of the study that the overall risk level category at the gas pipeline installation stage is Acceptable from 112 types of hazards, the average value of the overall probability, exposure and consequence of 13.40% with the total risk reduction of 72.62%.